2017
DOI: 10.1017/ppr.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

Stepping Stones to the Neolithic? Radiocarbon Dating the Early Neolithic on Islands Within the ‘Western Seaways’ of Britain

Abstract: The western seaways -an arc of sea stretching from the Channel Islands in the south, up through the Isles of Scilly, the Isle of Man, and the Outer Hebrides to Orkney in the north -have long been seen as crucial to our understanding of the processes which led to the arrival of the Neolithic in Britain and Ireland in the centuries around 4000 cal BC. The western seaways have not, however, been considered in detail within any of the recent studies addressing the radiocarbon chronology of the earliest Neolithic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…2600 cal BC (at 95 per cent confidence) (the latter phases of the site are currently not well defined chronologically; Garrow et al . 2017a: 115; see also Copper & Armit 2018). The best-preserved layers contained stone walls, stone-built hearths, postholes and spreads of occupation debris including 22 000 sherds of pottery.…”
Section: Neolithic Crannogsmentioning
confidence: 98%
See 1 more Smart Citation
“…2600 cal BC (at 95 per cent confidence) (the latter phases of the site are currently not well defined chronologically; Garrow et al . 2017a: 115; see also Copper & Armit 2018). The best-preserved layers contained stone walls, stone-built hearths, postholes and spreads of occupation debris including 22 000 sherds of pottery.…”
Section: Neolithic Crannogsmentioning
confidence: 98%
“…Consequently, some scholars have suggested that there may have been a surge in social competition due to pressure on land (Sharples 1992: 327; Armit 1996: 76).
Figure 4.Distribution of known Early/Middle Neolithic tombs, ‘settlements’ (with buildings), ‘occupation sites’ (more ephemeral traces of settlement) and islet sites in the Outer Hebrides, with key sites labelled (data from Canmore.org.uk and Garrow & Sturt 2017). Contains OS data © Crown copyright and database right 2019.
…”
Section: The Neolithic Of the Outer Hebridesmentioning
confidence: 99%
“…It is difficult to say a great deal about the third site to have produced BVSG cordons pottery, at L'Ouzière, Jersey, since it has not been excavated; external residues on the pottery produced a date of c .5050–4850 cal BC (Garrow et al . ). However, if, as it seems, it is indeed an occupation deposit without any associated features, again this would place it in a minority category of site for this period on the mainland.…”
Section: The Earlier Neolithic In the Channel Islandsmentioning
confidence: 97%
“…While the Neolithic of the Channel Islands is very well known for its monumental record, when dealing with the Earlier Neolithic the evidence from tombs does not feature much at all. With the single exception of the Les Fouaillages long mound (whose earliest phases date to c .4940–4720 cal BC; see Garrow et al ), the earliest tombs on the islands (passage graves) would probably have been constructed after c .4300 bc (e.g. Schulting et al .…”
Section: Later Mesolithic and Earlier Neolithic Evidence From The Chamentioning
confidence: 99%
“…This paper focuses on the introduction of agriculture into Wales, a predominantly mountainous area in western Britain. Situated at the intersection between several regions, notably the Irish Sea Zone to the west and mainland Britain to the east, Wales represents an important area for understanding the onset and diffusion of the Neolithic (eg, Lynch 2000;Sheridan 2007;McLaughlin et al 2016;Garrow et al 2017). However, Neolithic farming practices in Wales have received very little attention and there has been an over-reliance on evidence from a handful of wellknown sites.…”
mentioning
confidence: 99%